Plan de negocios para la creación de una empresa sobre importación de hortensias desde Colombia - Martínez Pachacama, Katherine Michelle (2019)
The hydrangeas are considered in different countries of the world as a flower variety that provides elegance and thus tend to be the most sought after when decorating important events, it is by this means that the idea of implementing this service in the Ecuador looking for the acceptance of the people having through it a good experience and elegance that this type of flower provides. The flower market is very broad in Ecuador and highly profitable, especially with roses which are the best known and accepted by Ecuadorians, the specific objective of this thesis plan is that hydrangeas become so well known and quoted as is the flower. To achieve this goal, an extensive study was carried out to see the feasibility and profitability of the project presented. In the first place, an investigation was carried out of the different external factors that help or, failing that, affect the project so that it can be successful. Second, different analyzes were carried out using quantitative and qualitative methods, conducting interviews with experts and surveys of potential potential consumers. In third place, the analysis of place, promotion price and product was carried out. Followed by the organizational structure of said company focusing on the import and production of the product. And to conclude a detailed financial plan was made with all the income and expenses of the company, for this indirect and direct costs were taken into account in order to perfect the end of the income statement of the Decoration Service Company.